Ultrasonographic Examination Results in the Screening of the Developmental Hip Dysplasia Babies Between Four Weeks to Six Months - Zehir, Sinan; Işıkan, Uğur Erdem; Sipahioğlu, Serkan; Sipahioğlu, Sevgi Temiz; Koruk, İbrahim (Fırat University, 2013)
Objective: The aim of this study is to assess regional incidence of developmental dysplasia(DDH) between four weeks and six months age of infants by ultrasonographic evaluation(Graf Method) and to determine the effectivity of ultrasonography in the early diagnosis of developmental dysplasia of hip. Materials and Methods: This study was conducted on 1127 newborns that applied to Children Hospital and Harran University Hospital in between February 2008 and March 2009 for non orthopedics reasons Babies older than 4 week and younger than 6 months were evaluated with hipultrasonography. Results: Ultrasonography performed 2254 hips were classified according to Graf classification; 1100( 48.8 %) hips were type Ia, 758(33.6 % ) hips were type Ib, 215(9.53 %) hips were type IIa, 55(2.4 %) hips were type IIb, 51(2.26 %) his were type IIc, 4( 0.17 %) hips were type D and 71(3.14 %) hips were type III-IV. Important risk factors determined in DDH cases were swaddling 81.6 %, female gender 72.5 %, first born 46.4 %, home delivery 19 %, positive family history 14,7 % and breech presentation 4,2 %. The incidence of DDH was significantly higher in the babies that had a congenital orthopaedic disorder. Conclusion: The most important prognostic factor for the threament of DDH is early diagnosis with hip-ultrasonography.As we face with DDH as a public health problem in our country, if you consider the regions that screening cannot be performed, ultrasonography can be discussed as an alternative diagnosis method in the cases where risk factors were determined.

Amaç: Dört haftalıktan büyük altı aylıktan küçük bebeklerin kalça incelemesinde ultrasonografi(Graf yöntemi) kullanarak Gelişimsel Kalça Displazisi( GKD) bölgesel insidansının saptanması ve yenidoğanlarda GKD'nin erken teşhisinde ultrasonografi ile yapılan tarama çalışmasının etkinliğinin belirlenmesidir. Gereç ve Yöntem: Çalışma Şubat 2008 ile Mart 2009 tarihleri arasında çocuk ve Harran Ü. Tıp Fak Araştırma hastanesine travma ve ortopedi dışı nedenler ile başvuran dört haftalıktan büyük altı aylıktan küçük 1127 yenidoğan bebek ultrasonografik olarak değerlendirildi. Bulgular: Ultrasonografi yapılan 2254 kalça Graf sınıflandırmasına göre değerlendirildiğinde 1100(%48.8) kalça tip Ia, 758(%33.6) kalça tip Ib, 215(%9.53) kalça tip IIa, 55(%2.4) kalça tip IIb, 51(%2.26) kalça tipIIc, 4(%0.17) kalça tip D ve 71(%3.14) kalça tip III-IV olarak tespit edildi. GKD'li olgularda tespit edilen önemli risk faktörleri; kundak uygulaması %81.6, kız cinsiyet %72.5, ilk bebek olma %46.4, evde doğum %19, pozitif aile hikayesi %14.7, makat geliş %4.2 şeklindeydi. Doğumsal ortopedik bir hastalık bulunan bebeklerde GKD görülme riski ortopedik hastalığa olmayanlara göre anlamlı olarak daha fazla tespit edildi. Sonuç: Günümüzde güncelliğini korumaya devam eden GKD tedavisinde ilk ve en önemli koşul erken tanıdır. Hastalığın bir halk sağlığı problemi olarak karşımıza çıktığı ülkemizde genel tarama yapılamayan bölgelerde, kalça ultrasonografisinin uygulanması GKD'ye ilk yaklaşımda alternatif bir yöntem olarak tartışılabilir.
Dört Hafta- Altı Ay Arası Bebeklerde Gelişimsel Kalça Displazisi Taramasında Ultrasonografik Çalışma Sonuçları